Education And Training Management Of Supervisors Leadership To Improve The Quality Performance Implementation Of Change Action In Police Organization - Mustofa, Bisri; Trisnamansyah, Sutaryat; Hanafiah; Karim Fatkhulloh, Faiz (International Journal of Educational Research & Social Sciences, 2022)
Forming an ASN figure is not as easy as imagined, especially in the era of globalization as it is today. An ASN is expected to have toughness and professionalism as a state servant and public servant, especially in service to the community. The formation and development of a change leader model in this PKP is certainly not an easy process. The challenges for the education and training organizers include changing the mindset of the PKP participants after the training in implementing change actions within the police organization. The purpose of this study is to find the concept of supervisory leadership training management to improve the performance quality of implementing change actions within the Police organization. The educational theory that is used as the basis for this dissertation is Dewey's educational theory which holds that education is growth, development, life; Edward Sallis's theory of quality is that quality must be implemented in an integrated manner, involving all components of the organization, to continuously improve quality in order to satisfy customers. Management theory George R. Terry divides four basic functions of management, namely planning (planning), organizing (organizing), implementation (actuating) and assessment (evaluating). The method used in this research is descriptive analysis method, with the aim of maintaining the integrity of the subject, the data collected is studied as an integrated whole. Data collection techniques were carried out by (1) Observation, (2) Interview and (3) Documentation. The results of the research show that the management of education and training has beencarried out although there is still a need for a better arrangement from time to time and experience in the implementation of training which is certainly sustainable. PKP policies and programs need to be restructured and re-functioned in the post-training monitoring and evaluation section so that they are fully functional in the context of implementing change actions. Implementation will motivate participants to do something if they feel confident that they will be able to, believe that the work will benefit them. Learning assessment conducted for training participants is a stage to measure abilities as input in making specific decisions. The problem of improving the quality of action for change and public service innovation in its implementation does not always run smoothly because there are many challenges and obstacles to be faced. Actualization of the basic values of quality commitment in carrying out the duties of the apparatus as a solution that can encourage the creation of a superior work climate or culture that can foster courage to display creativity and innovation for change actions.